2001
DOI: 10.1021/es0013935
|View full text |Cite
|
Sign up to set email alerts
|

Time Resolved Characterization of Diesel Particulate Emissions. 1. Instruments for Particle Mass Measurements

Abstract: The measurement of diesel vehicle exhaust particulate mass is currently accomplished using filter collection methods according to the Code of Federal Regulations (CFR). Such filter methods limit time resolution to a minimum of several minutes, making it impossible to study emissions during transient operating conditions. Extensive testing of five different measurement methods has demonstrated that fast response measurements of diesel exhaust particulate mass concentrations, consistent with CFR filter measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 29 publications
6
63
0
Order By: Relevance
“…By volume, the standard consists of 1-3% particles with diameters less than 1 m, 36 -44% with diameters less than 4 m, 83-88% with diameters less than 7 m, and 97-100% with diameters less than 10 m. Niu et al 25 found that in comparing data from four DustTraks collocated in an indoor environment, the interinstrument variability was a reasonable 3%. Several authors have also reported that DustTrak measurements correlate well with filter-based measurements of diesel exhaust, 26 ambient urban particulate matter, 27 and indoor airborne particles, 25 though in all cases, investigators noted that the DustTrak deviated from filter-based measurements by a factor that depends on the nature of the aerosol measured. One shortcoming of using a nephelometer-style instrument is that light scattering response to changes in mass concentration can depend strongly on particle composition as well as particle size.…”
Section: Field Measurementsmentioning
confidence: 95%
“…By volume, the standard consists of 1-3% particles with diameters less than 1 m, 36 -44% with diameters less than 4 m, 83-88% with diameters less than 7 m, and 97-100% with diameters less than 10 m. Niu et al 25 found that in comparing data from four DustTraks collocated in an indoor environment, the interinstrument variability was a reasonable 3%. Several authors have also reported that DustTrak measurements correlate well with filter-based measurements of diesel exhaust, 26 ambient urban particulate matter, 27 and indoor airborne particles, 25 though in all cases, investigators noted that the DustTrak deviated from filter-based measurements by a factor that depends on the nature of the aerosol measured. One shortcoming of using a nephelometer-style instrument is that light scattering response to changes in mass concentration can depend strongly on particle composition as well as particle size.…”
Section: Field Measurementsmentioning
confidence: 95%
“…It was equipped with a comprehensive suite of state-of-the-art fast response instruments, including an aethalometer (AE-16, Magee Scientific) for BC; a photoionization aerosol sensor (EcoChem PAS 2000CE) for particle-bound PAHs; a non-dispersive infrared (NDIR) unit (Li-Cor LI 6262) for carbon dioxide (CO 2 ); an Aerodyne tunable infrared laser differential absorption spectrometer (TILDAS) for nitrogen dioxide (NO 2 ) and formaldehyde (HCHO); an NDIR analyzer for carbon monoxide (CO); a chemiluminescent analyzer (Thermo 42C) for nitrogen oxides (NO x ); a proton transfer reaction mass spectrometer (PTR-MS) for speciated volatile organic compounds (VOCs); and an aerosol photometer for PM 2.5 (TSI DustTrak 8520). Fast results for the aethalometer, which recorded measurements at one-minute intervals, were obtained by applying the time signature of the aerosol photometer data, as previous results have shown a strong correlation between BC and DustTrak measurements (Moosmüller et al, 2001). In strict terms, the chemiluminescent analyzer was configured to detect total reactive nitrogen species (NO y ); however NO x accounts for nearly all of NO y in fresh vehicle exhaust.…”
Section: Mobile Laboratorymentioning
confidence: 99%
“…The method depends on scattering efficiencies, which are a function of particle size distributions and optical properties. Although scattering efficiencies of ambient and diesel particles are similar (Waggoner et al, 1981), the efficiencies may differ for gasoline particles; and the calibration for individual vehicles may vary by a factor of two or more (Moosmüller et al, 2001). …”
Section: Mobile Laboratorymentioning
confidence: 99%
“…A number of articles and reports have been published regarding the contribution of traffic to OC and EC in Europe and the USA (Kerminen et al, 1997;Miguel et al, 1998;Fraser et al, 1999;Moosmüller et al, 2000;Shi et al, 2000;Kohler et al, 2001;Ruellan et al, 2001). …”
Section: Introductionmentioning
confidence: 99%